Mitochondrial Genome Evolution and a Novel RNA Editing System in Deep-Branching Heteroloboseids. (1st May 2017) - Yang, Jiwon; Harding, Tommy; Kamikawa, Ryoma; Simpson, Alastair G.B.; Roger, Andrew J.
Abstract : Discoba (Excavata) is an evolutionarily important group of eukaryotes that includes Jakobida, with the most bacterial-like mitochondrial genomes known, and Euglenozoa, many of which have extensively fragmented mitochondrial genomes. However, little is known about the mitochondrial genomes of Heterolobosea, the third main group of Discoba. Here, we studied two heteroloboseids—an undescribed amoeba "BB2" and Pharyngomonas kirbyi . Phylogenomic analysis revealed that they form a clade that is a sister group to all other Heterolobosea. We characterized the mitochondrial genomes of BB2 and P. kirbyi, which encoded 44 and 48 putative protein-coding genes respectively. Their gene contents were similar to that of Naegleria . In BB2, mitochondrially encoded RNAs were heavily edited, with ∼500 mononucleotide insertion events, mostly guanosines. These insertions always have the same identity as an adjacent nucleotide. Editing occurs in all ribosomal RNAs and protein-coding transcripts except one, and half of the transfer RNAs. Analysis of Illumina deep-sequencing data suggested that this RNA editing is very accurate and efficient, and most likely co-transcriptional. The dissimilarity of this editing process to other RNA editing phenomena in discobids, as well as its apparent absence in P. kirbyi, suggest that this remarkably extensive system of insertional editing evolved independently in the BB2 lineage, after its divergence from the P. kirbyi lineage.